Increased serum oxidized low-density lipoprotein levels in pregnancies complicated by gestational diabetes mellitus - Azam Ghaneei; Sara Yassini; Mohammad Ebrahim Ghanei; Ahmad Shojaoddiny-Ardekani (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Elevated serum levels of oxidized Low-density Lipoprotein (oxLDL) have been found in type 2 and in poorly controlled diabetic patients. Gestational diabetes mellitus (GDM) has common features with type 2 diabetes. Objective: The aim of our study was to evaluate the serum levels of oxLDL in women with GDM compared to normal pregnant women. Materials and Methods: In this cross-sectional study, ninety-two subjects were randomly allocated to either GDM (n=46) or control (n=46) groups matched for age, body mass index and parity from March 2013 to March 2014. GDM was diagnosed according to the American Diabetes Association criteria at 24-26 weeks of gestation. OxLDL was measured using enzyme-linked immunosorbent assay. T-test and Pearson correlation coefficients were applied for analyzing the data by using SPSS version 17. Results: Compared to the controls, significantly higher oxLDL levels were found in the GDM group (17.16 ± 3.71 U/L vs. 8.77 ± 1.84 U/L, respectively, p < 0.001). No significant correlations were found between oxLDL and age and BMI of the patients in the groups. Conclusion: Our study found significant increase of oxLDL in GDM emphasizing the role of short-term hyperglycemia in the formation of oxLDL during GDM. The importance of aptly diagnosis of GDM in maternal health may also be concluded.